Status Resistensi Aedes aegypti (Linn.) terhadap Organofosfat di Tiga Kotamadya DKI Jakarta - Endang Setiyani; Heni Prasetyowati; Joni Hendri; Tri Wahono (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2016)
High cases of dengue fever in Jakarta lead to increased insecticides usage in Aedes aegypti control activity. Malathion and temephos are the most frequent used insecticide in Jakarta. These insecticides derived from organophosphates class. This sudy aimed to know the resistance status of Ae. aegypti in three municipalities in Jakarta to malathion 0.8 % and temephos 0.02 ppm. This study was an observational study with cross-sectional design. Research sites consisted of three municipalities i.e. East Jakarta, West Jakarta and South Jakarta. Each municipality represented by three public health centers. The study population were all houses located in highest endemic ares in each health centers. Larvae survey was conducted in 100 houses in each area. Collected larvae was then colonized to 3rd generation. Test of susceptibility to malathion 0.8 % was done using impregnated paper refers to the WHO method, whereas temephos susceptibility test was conducted in accordance with Elliot method. The result showed that Ae. aegypti in all research areas have been resistant totemephos 0,02 ppm and malathion 0.8 %. The usage of malathion and temephos in long term caused the resistance of Ae. aegypti. Need replacement insecticide with the active ingredient that is pr oven its effectiveness as well as increased mosquito eradication efforts in the community.